Alternative Organic Liquid Fertilizer from Meatball Water Decoction with Banana Humps Activator - S. D. Cahyani; N. R. Amalia; A. H. Achmad; M. Hilmi; D. Triasih (Jurnal Sain Peternakan Indonesia, 2019)
This study aimed to determine the effect of the use of EM4 and Local Microorganism (LM) activators from banana hump (Kepok banana, Raja banana, and Ambon banana) on the manufacture of organic liquid fertilizer derived from waste meatball water stew. The research method used in this study was Completely Randomized Design (CRD) consisting of 4 treatments and three replications, namely: P1 EM4, P2 (Local Microorganism from Kepok banana hump ), P2 (Local Microorganism from Ambon banana hump), P3 (Local Microorganism from Raja banana hump). In this study testing the levels of Nitrogen, Phosphorus, Potassium, Carbon, and pH levels in organic liquid fertilizer from boiled meatball water. The data obtained from this study were analyzed using Complete Randomized Design and Duncan's advanced test. The results of the addition of EM4 activator and banana hump MOL on the manufacture of organic liquid fertilizer from meatball decoction water showed no significant effect (P> 0.05) on N, K, and pH levels on fertilizers. The results showed a significant effect (P <0.05) on the P content of fertilizer. The highest C content was found in P2, while the highest C / N ratio was found in P0.